From metaphor of slavery to metaphor of freedom: Article 18 and the incorporation of migrant prostitutes into Italian society - Testaî, Patrizia (2008)
This thesis is concerned with the debate on 'trafficking in persons' as a new form of slavery. It will explore the concept of slavery both historically and in its links with contemporary migration and connected issues of gender, sexuality, and labour exploitation. Within the contemporary debate on 'trafficking', attention has focused in fact predominantly on migrant women and girls involved in sex work and described as 'victims of trafficking for the purpose of sexual exploitation'.